Prevalencia de anticuerpos para el virus de rinotraqueitis bovina infecciosa en ganado de carne en Colombia y aislamiento del virus de casos clínicos - Aycardi B., Eduardo R.; Sanclemente, V.; Cortés, J.M. (1978)
A passive haemagglutination test for evaluation of antibodies from Infectious Bovine Rhinotracheitis Virus was used. Beef cattle serum from four cattle regions of Colombia were analyzed. In the Eastern Plains and average prevalence of 19.5 percent was obtained when 48 farms were examined, from a total of 3.555 serum samples. Only 4 farms from this group did not have reactors. From the Caquetá Department, south-central region of the country, 30 farms (472 animals) were sampled, and an average prevalence of 24.5 percent was obtained. No reactors were found in 3 of these farms, the others had one or more reactors. In 39 cattle farms of the Departments of Sucre and Córdoba in the north-west of the country, 1.826 serum samples were taken for examinaiton, and an average of 13.5 percent reactors was found. In 7 farms there were no reactors. In the cattle region located in the Cauca Valley, south-west of the country, samples from 929 animals from 25 ranches were obtained. Seven animals were found with titers, which is equivalent to an average of 0.75 percent positivies: these reactors came from 4 ranches. Complementary of this, six isolations of IBR virus were made from animals with medium to high titles, located in a ranch from the Easten Plains of Colombia. The wide dissemination of antibodies observed supports the believe that the virus was introduced to the country many years ago. However the virus is not producing clinical sindromes similar to those reported from countries in temperate climates. It appears that the virus is associated with mild respiratory problems, abortions, and infertility in beef cattle. The role that this virus plays in diminishing beef cattle productivity, must be throughly investigated. Studies must be made to determine the control measures that can be used in the special conditions of the tropical areas